The Thyroid Hormone-target Gene Rhes a Novel Crossroad for Neurological and Psychiatric Disorders: New Insights from Animal Models. (1st August 2018) - Napolitano, Francesco; D'Angelo, Livia; de Girolamo, Paolo; Avallone, Luigi; de Lange, Pieter; Usiello, Alessandro
Highlights: The striatum-enriched protein Rhes is developmentally regulated by thyroid hormone. Rhes modulates striatal dopamine-dependent transmission. Rhes influence neurological and psychiatric phenotypes in animal models. Abstract: Ras homolog enriched in striatum (Rhes) is predominantly expressed in the corpus striatum. Rhes mRNA is localized in virtually all dopamine D1 and D2 receptor-bearing medium-sized spiny neurons (MSNs), and cholinergic interneurons of striatum. Early studies in rodents showed that Rhes is developmentally regulated by thyroid hormone, as well as by dopamine innervation in adult rat, monkey and human brains. At cellular level, Rhes interferes with adenosine A2A- and dopamine D1 receptor-dependent cAMP/PKA pathway, upstream of the activation of the heterotrimeric G protein complex. Besides its involvement in GPCR-mediated signaling, Rhes modulates Akt pathway activation, acts as E3-ligase of mutant huntingtin, whose sumoylation accounts for neurotoxicity in Huntington's disease, and physically interacts with Beclin-1, suggesting its potential involvement in autophagy-related cellular events. In addition, this protein can also bind to and activate striatal mTORC1, one of the key players inl -DOPA-induced dyskinesia in rodent models of Parkinson's disease. Accordingly, lack of Rhes attenuated such motor disturbances in 6-OHDA-lesioned Rhes knockout mice. In support of its role in MSN-dependent functions, several studies documented that mutant animals displayed alterations in striatum-related phenotypes reminiscent of psychiatric illness in humans, including deficits in prepulse inhibition of startle reflex and, most interestingly, a striking enhancement of behavioral responses elicited by caffeine, phencyclidine or amphetamine. Overall, these data suggest that Rhes modulates molecular and biochemical events underlying striatal functioning, both in physiological and pathological conditions.